PERFORMA REPRODUKSI INDUK SAPI BALI DI KECAMATAN LOLONGGUBA KABUPATEN BURU - Adinda Risky Nila Suparto; Jusak Labetubun; Isak P. Siwa (PT. BARRINGTONIA ASIATICA LESTARI, 2026)
This research was prepared with the main aim of assessing and analyzing the reproductive performance of female Bali cattle raised by breeders in Lolongguba District. Determining the research area and selecting participants was carried out using a field survey approach, with the application of purposive sampling techniques, namely based on certain criteria that were relevant to the research objectives. The research location focused on three villages that were considered representative, namely Grandeng Village, Waegeren Village, and Wanakarta Village. The reproductive variables or parameters observed in this study include several important indicators, including the age of first mating in female Bali cattle, the conception rate or calving rate, the birth rate or calving rate, the time when lust appears after giving birth which is known as post partum estrus, the time between births or calving interval, and the calf death rate before weaning or pre-weaning mortality. The research results show that the average age of first mating for female Bali cattle is in the range of 1,94 ± 0 years. The conception rate obtained reached 81.72%, while the birth rate was recorded at 94,48%. In addition, the average postnatal estrus time 4,9 ± 0,6 and calving interval were each in the range of 13,9 ± 0.6 months, and, a pre-weaning mortality rate of 8,74%. These findings provide a general overview of the condition and reproductive performance of female Bali cattle in the study area.